KEABSAHAN PERKAWINAN DENGAN PENETAPAN WALI ADHAL DIHUBUNGKAN ASAS-ASAS PERADILAN AGAMA DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Nur Fitri Melnia; Djanuardi; Hazar Kusmayanti (JURNAL ILMIAH LIVING LAW, 2023)
Marriage requirements must be fullfiled by the prospective bride and groom before marriage, but when it does not fulfill the requirements one of that the refusal of the marriage guardian called Islamic law wali adhal, then marriage registration cannot be conducted. First study aims to determine the legal certainty and validity of the marriage of guardian adhal according the law of Islamic and Marriage law. The second aims to find out and analyze the implementation of the principles of the Religious Justice in determining the guardian adhal in the practice of the settlement process and the judges considerations at the Bogor Religious Court. The object of journal is determination 0242/Pdt.P/2017/PA.Bgr and 57/Pdt.P/2021/PA.Bgr. The first result study is show the marriage registration with the determination of adhal guardian which was granted by the judge valid in the point of Islamic law. Marriage Law tell the marriage registration is legal but the marriage guardian hasn’t been regulated. The second result study is stated with related number determination was inkrah because judges at the Bogor Religious Court made considerations through the relevant principles of the Judicial Law namely is Islamic personality, legality, equality and active judges providing assistance.  Keywords : Wali Adhal; Determination; Registration.